The Effect Of Current Ratio (CR), Total Assets Turnover (TATO), Debt To Equity Ratio (DER), Net Profit Margin (NPM) On Changes In Profit In The Food And Beverage Sub-Sector Manufacturing Industry On The Indonesian Stock Exchange, 2016-2021 - Rahmadia Martin; Elsa Meirina (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine the impact of the dependent variable on profit changes with the four independent variables consisting of the current ratio, total asset turnover, debt to equity ratio and net profit margin. This type of research used is a quantitative method. The samples used were 11 food and beverage companies listed on the Indonesia Stock Exchange in 2016-2021. The sampling technique used is purposive sampling. The data analysis method used is multiple linear regression analysis using the SPSS 22 program. The results showed that the current ratio has a negative effect on changes in earnings and total asset turnover, debt to equity ratio, net profit margin has no effect on changes in profits.